A library of dimeric and trimeric phthalonitriles linked by a single aromatic ring: comparative structural and DFT investigations. Issue 8 (3rd February 2016) - Köç, Muzaffer; Zorlu, Yunus; İşci, Ümit and Berber, Savaş and Ahsen, Vefa and Dumoulin, Fabienne
Abstract : A library of five phthalonitriles, dimeric or trimeric, all connected by an aromatic spacer, was selected to be comparatively studied from a structural point of view. Abstract : A library of five phthalonitriles, dimeric or trimeric, all connected by an aromatic spacer (catechol, resorcinol, hydroquinone, phloroglucinol and catechol with two tert -butyl moieties), was selected to be comparatively studied from a structural point of view. Hirshfeld surface analysis and DFT calculations were performed as well.